The Right to Information Act in Bangladesh: An Analysis in the Light of Johannesburg Principles of Freedom of Information Legislation - Murad, Mohammad Hasan; Hoque, Kazi Arshadul (IIUC Studies, 2012)
Today's knowledge based world is now resonating with the call for meaningful democracy backed by transparency and accountability in the state engine and peoples right of access to information has gained a great importance. In a modern democratic state, the right to information, more popularly described as the right to know, is an indispensable prerequisite. There is no denying the fact that the notion of freedom of thought, of conscience, of speech and rule of law become worthless if the people are deprived of access to information. There appears to have been a universal recognition of the demand and necessity for the establishment of peoples right of access to information. The experience in other countries suggests that this scenario can be changed by empowering people with right to information or freedom of information. The translation of right to information into law has to be done considering a number of principles which are required to be addressed in the law. The article presents an overview of the concept of right to information and attempts to discuss the principles underpinning right to information along with an analysis of to what extent those principles are reflected in the right to information law of Bangladesh. DOI: http://dx.doi.org/10.3329/iiucs.v7i0.12261 IIUC Studies Vol.7 2011: 73-90